Factors influencing prosthesis satisfaction among first time lower-limb prosthetic users from Wentworth Hospital in KwaZulu-Natal - Ramdeen, Joshika Diyajal (Stellenbosch : Stellenbosch University, 2023)
Thesis (MHumanRehabSt)--Stellenbosch University, 2023.